2001
DOI: 10.4269/ajtmh.2001.64.293
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex polymerase chain reaction amplification and differentiation of Entamoeba histolytica and Entamoeba dispar DNA from stool samples.

Abstract: Abstract. Due to the clinical importance of differentiating the two species of the Entamoeba histolytica/Entamoeba dispar complex, we developed a multiplex polymerase chain reaction (PCR) method that overcomes time-consuming and laborious procedures. We report here a DNA extraction protocol using non-fixed stool samples that avoid long lysis-incubation periods through the combined use of zirconium beads and a lysis-supporting buffer. We characterized 49 of 52 stool specimens from Cuban patients with amoebiosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 37 publications
(38 reference statements)
1
10
0
2
Order By: Relevance
“…Based on these results, PCR amplification was carried out on all 111 DNA samples at loci 1-2, 3-4, and 9-4 and at half locus [16][17][18][19]. In the final analysis, DNA from 11 of the 111 samples failed to amplify at any of these four loci.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, PCR amplification was carried out on all 111 DNA samples at loci 1-2, 3-4, and 9-4 and at half locus [16][17][18][19]. In the final analysis, DNA from 11 of the 111 samples failed to amplify at any of these four loci.…”
Section: Resultsmentioning
confidence: 99%
“…Species-specific primers that amplify regions of several different genes have been used (1,7,14,17,18,19). Using trophozoites in culture, comparisons showed that PCR is more sensitive and specific than the enzyme-linked immunosorbent assay-based stool antigen detection kits, which employ monoclonal antibodies for the detection and differentiation of E. histolytica and E. dispar (16).…”
mentioning
confidence: 99%
“…Several PCR assays designed to differentiate E. histolytica for E. dispar have been described [5,6,21,[22][23][24][25]32,33]. Most of them targeted either the small subunit ribosomal RNA gene or specific episomal repeats species.…”
Section: Discussionmentioning
confidence: 99%
“…In reference laboratories, PCR is the method of choice for differentiation between the pathogenic specie (E. histolytica) from the non-pathogenic (E. dispar). Many investigations have reported successful application of PCR to the diagnosis of amoebiasis as a tool for final confirmatory identification of intestinal amoebiasis [5,6,[20][21][22][23][24][25][26].…”
mentioning
confidence: 99%
“…No reduction in the ability to perform PCR amplifications of E. histolytica DNA fixed in 1 to 10% formalin was noted for 7 days (169). Núñez et al (141) described multiplex PCR amplification for the detection and characterization of both E. histolytica and E. dispar in stool samples by using two pairs of specific primers combined in a single reaction mixture. This novel approach had 94% sensitivity and 100% specificity.…”
Section: Molecular Biology-based Diagnostic Tests and Pcrmentioning
confidence: 99%